Multivalent vaccine candidate from conserved immunogenic peptides in entry or exit proteins of Orthopoxvirus genus - Leonardo Pereira de Araújo; Evandro Neves Silva; Severino Matias de Alencar; Patrícia Paiva Corsetti; Leonardo Augusto de Almeida (Scientific Reports)
Abstract Orthopoxvirus (OPXV) genus includes emerging and re-emerging zoonotic viruses that pose threats to global health. Smallpox caused pandemics in the 20th century. Borealpox was responsible for a death in Alaska in 2024. Mpox, declared a Public Health Emergency by the WHO in 2022, with an alert reclassification in 2024. The lack of effective therapies and the limitations of attenuated virus vaccines, especially for immunocompromised individuals, reinforce the urgent need for new strategies to prevent diseases caused by pathogens of the OPXV genus. This study aimed to identify conserved epitopes in proteins essential for the entry and exit of these viruses and, based on this identification, develop a promising multivalent vaccine candidate. Viral protein sequences were extracted from the NCBI Virus database, and 160 sequences were analyzed to identify conserved epitopes using the Immune Epitope Database. After filtering the data, epitopes were concatenated to create a chimeric multi-epitope protein combined with β-defensin and PADRE adjuvants. The resulting protein, with eight conserved epitopes covering all OPXV viruses (including Mpox Clade Ib), was evaluated for antigenicity, allergenicity, and structural stability. It showed strong interaction with the TLR2 receptor, along with good predictions for immune responses after three doses. This proposed multivalent vaccine represents a potential approach against these zoonotic viruses, with promising results for in vitro and in vivo studies.